1460 Acid and Non Acid Gastroesophageal Reflux in Critically Ill Mechanically Ventilated and Tube-Fed Infants. (October 2012) - Hallal, C; Manica, D; Chaves, VS; Marostica, P; Trotta, EA; Carvalho, PA; Fontella, FU; Matte, US; Barros, SGS; Goldani, HAS
Abstract : Background and Aims: Critically ill patients mechanically ventilated have high risk of gastroesophageal reflux (GER) and pulmonary aspiration. We aimed to evaluate the characteristics of acid and non acid GER in critically ill infants undergoing mechanical ventilation. Patients and Methods: Twelve infants undergoing mechanical ventilation suffering from severe bronchiolitis were enrolled. They were sedated, off any antiacid secretory medicines and on full enteral nutrition. They underwent MII-pH study by using equipment Sleuth-Sandhill Scientific, USA. Data were manually analyzed by using software BioVIEW Analysis version 5.6 (Sandhill Scientific). Parameters analyzed were: number of total episodes of GER (NGER); height of refluxate [proximal (PGER) or distal (DGER)]; reflux content [acid (AGER) or non acid (NAGER)]; and acid reflux index (ARI) - % of time pH is under 4- considered altered when ARI is >10%. Data were analyzed by Wilcoxon test. Results: Overall median age was 3 months (range 1–12m), 9 males. Only two patients had ARI above 10%. There were 362 GER episodes. Median NGER of each patient was 29.5(3–77). There was significant difference between PGER and DGER [23.5(7.2–36.2) vs 6.0(5.0–9.0), p=0.003] and between acid and non acid DGER [0.0 (0.0–2.7) vs 6.0(2.5–7.7), p=0.036). There was no significant difference between acid and nonacid NGER and between acid and non acid PGER. Conclusion: Proximal GER was more significant than distal GER and there was no difference between acid and non acid content. This finding reinforces the risk of pulmonary aspiration of both acid and non acid reflux in infants undergoing mechanical ventilation.